Identification of major drivers and roadblocks for remanufacturing in India. (20th January 2016) - Sharma, Vaishali; Garg, Suresh K.; Sharma, P.B.
Abstract: Remanufacturing is "an industrial process in which a worn out product is restored to as good as new condition". In contrast, a repaired or rebuilt product normally retains its identity, and only those parts that have failed or are badly worn are replaced or serviced. Remanufacturing is becoming the paradigm expression for product recovery management by manufacturing "as good as new" products after its end of life or end of use. In the present business environment remanufacturing has distinct advantages: on one side, it provides equipment at an economical cost and on the other side, it makes for environment friendly manufacturing. In spite of several other advantages, remanufacturing is not catching up, as it should have been in India, and various authors have listed different reasons. The aim of the present study is to explore the major drivers and roadblocks for remanufacturing in India. A questionnaire-based survey was conducted to identify the key economic, environmental and social drivers of remanufacturing. This was followed by the identification of the major roadblocks and it was observed that competitive pricing is the most important economic driver, whereas environmental driver was identified as the best way of product recovery. Quality concerns, no guidelines related to remanufacturing and lack of government support are identified as major roadblocks for remanufacturing in India.